DEVELOPMENT OF MULTIMEDIA LEARNING OF COEFFICIENT PERFORMANCE INSPECTION IN THE LESSON OF AIR CONDITIONING SYSTEM AND INSTALLATION IN PANDEMIC COVID-19 - Maulana, Muhammad Farhan; Sumardi, Kamin; Rohendi, Dedi; salman, Fachrurrazi (Universitas Pendidikan Indonesia, 2021)
Air conditioning system and installation is one of the subjects in the refrigeration and air conditioning program. One of the materials on the competency is basically explaining about the inspection of Coefficient of Performance (CoP). During this pandemic, students are required to study at home and do online learning. This online learning causes many students to pay less attention to the learning provided. Students are less interested in learning traditional methods because students are easily bored. Students only listen to and write material explanations with rough media. Research on media development is very important, in order to create a medium that is able to support interesting online learning. This research aims to produce proper multimedia learning for CoP examination materials and to know students' response to the application of multimedia in the subjects of the System and the installation of air system CoP inspection materials. The research method used by the agitation of the Research and Development (RD) method. The subject of research for the implementation of this media is students of SMKN 1 Cimahi who have studied cop examination materials. Sample for the implementation of 20 students. Judgement on media is done by media experts and materials experts, namely Lecturers in the Department of Mechanical Engineering Education and teachers at SMKN 1 Cimahi. The results of this study, that multimedia made is said to be feasible with the reference rating scale by experts with the percentage of assessments by media experts and material experts obtained that multimedia learning made is declared feasible, while the improvement of learning results is in the category of Good. Similarly, students' response to multimedia learning used is in a good category